Empowerment of Geddongnge Youth Group through the Development of IoT-Based Rooster Farming - Ahnaf Riyandirga Ariyansyah Putra Helmy; Moeh. Kay Muddin Asnur; Nurafni Oktaviyah; Mohammad Junaedy Rahman (Mattawang: Jurnal Pengabdian Masyarakat, 2026)
The rooster farming business in Geddongnge Village, Parepare City, holds significant economic potential, yet its growth is hampered by reliance on traditional coops and minimal monitoring management, frequently leading to high livestock mortality rates. This community engagement program zeroes in on boosting farmer productivity through innovative technology. The primary goal is to revitalize coops with a durable, modern, healthy design and implement an Internet of Things (IoT)-based monitoring system. We employed a participatory approach, which included socialization, comprehensive training, technology implementation, and ongoing mentorship. The practical solutions involved constructing galvanized iron coops with thermal insulation, installing cross-ventilation with an exhaust fan, and setting up temperature/humidity sensors and CCTV. The results demonstrate a potential for reduced livestock mortality, evidenced by the visibly healthier and improved condition of the roosters, marked by increased responsiveness and activity according to partner reports. This program successfully establishes an efficient and sustainable farming model.